Dorsal root ganglion stimulation for the treatment of joint pain with predominantly nociceptive characteristics: A case series. Issue 3 (8th December 2022) - Chapman, Kenneth B.; Tupper, Connor; Vissers, Kris C.; van Helmond, Noud; Yousef, Tariq
Abstract: Introduction: Dorsal root ganglion stimulation (DRG‐S) has recently emerged as a novel therapy in neuromodulation that demonstrated a higher rate of success than spinal cord stimulation (SCS) in a prospective, head‐to‐head randomized comparative trial to treat complex regional pain syndrome (CRPS) and causalgia. In contrast to SCS, DRG‐S also shows promise in treating conditions that are not purely neuropathic such as axial low back pain, which has a prominent nociplastic pain component. It is not known to what extent the effectiveness of DRG‐S for such indications is due to effective treatment of the neuropathic pain component versus the effects of DRG‐S on mechanical pain. Although rarely studied, reporting outcomes of DRG‐S to treat predominantly mechanical/nociceptive pain may help point toward expanding the utility of this therapy. Here, we present five cases of refractory mechanical pain treated with DRG‐S. Methods: A retrospective analysis of all patients who underwent a successful DRG‐S trial and implant between September 2017 and September 2021 at our institute was performed. Patients who had intractable joint pain without strong evidence of neuropathic pain were included in this case series. The Budapest criteria for CRPS, the Douleur Neuropathique 4 Questions (DN4) survey, or a definable nerve injury were used to determine the presence of neuropathic pain. Baseline assessments for pain (Numeric Rating Scale [NRS]), function (Oswestry Disability Index [ODI]), quality of life (EuroQol‐5 Dimension [EQ‐5D]), and other applicable joint surveys were extracted from pre‐trial baseline and follow‐up appointments. Results: Five patients were identified and included. Patient diagnoses consisted of refractory joint pain of the hip, knee, or ankle. Mean NRS pain scores improved by 74% from 9.2 at baseline to 2.4 at the last follow‐up (mean = 28 months post‐implant). From baseline to the last follow‐up, mean ODI scores improved by 65% from 66 to 23 and EQ‐5D scores more than doubled from an average of 0.371 to 0.797. Conclusion: This clinical report illustrates the potential utility DRG‐S has in treating pain that clinically presents as predominantly refractory mechanical joint pain without a significant neuropathic component. The physiological reasons for our observations may be that DRG‐S is able to directly influence the conduction of nociceptive signaling at the DRG and within the spinal cord. Further investigations are warranted to determine if DRG‐S is a potential treatment option for chronic mechanical pain.